Hypergroups Related to a Pair of Compact Hypergroups - Heyer, H.; Kawakami, S.; Tsurii, T.; Yamanaka, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
The purpose of the present paper is to investigate a hypergroup associated with irreducible characters of a compact hypergroup H and a closed subhypergroup H₀ of H with |H/H₀|<+∞. The convolution of this hypergroup is introduced by inducing irreducible characters of H₀ to H and by restricting irreducible characters of H to H₀. The method of proof relies on the notion of an induced character and an admissible hypergroup pair.